Measuring political instability at a high frequency - Niklas Benner; Boris Blagov; Maximilian W. Dirks (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
This study introduces the World Index of Political Instability (WIPI), a novel high-frequency measure that covers four dimensions of political instability in 182 countries, available from 1960 until 2024. Our measure is extracted from the curated texts of the Economist Intelligence Unit's Country Reports using text mining techniques, allowing us to track political instability on a high frequency while matching various established low-frequency proxies. We show that political instability has significant and negative short-run effects on the economy similar to a demand-side shock. In contrast to uncertainty shocks, the observed effects are not immediate but take up to one year until they materialize. The measured effects are stronger in low-income economies than in high-income economies and during recessionary periods. – – Diese Studie stellt den World Index of Political Instability (WIPI) vor, einen neuartigen, hochfrequenten Indikator, der vier Dimensionen politischer Instabilität in 182 Ländern abdeckt und für den Zeitraum von 1960 bis 2024 verfügbar ist. Unser Indikator wird mithilfe von Text-Mining-Techniken aus den kuratierten Texten der Länderberichte der Economist Intelligence Unit extrahiert, wodurch wir politische Instabilität mit hoher Frequenz verfolgen und gleichzeitig verschiedene etablierte niedrigfrequente Proxies abgleichen können. Wir zeigen, dass politische Instabilität erhebliche und negative kurzfristige Auswirkungen auf die Wirtschaft hat, ähnlich wie ein Nachfrageschock. Im Gegensatz zu Unsicherheitsschocks sind die beobachteten Auswirkungen nicht unmittelbar, sondern treten erst nach bis zu einem Jahr ein. Die gemessenen Auswirkungen sind in Volkswirtschaften mit niedrigem Einkommen stärker als in Volkswirtschaften mit hohem Einkommen und während Rezessionsphasen.
Keywords: C23; C55; O43; Z18; 330; Political Instability; Business Cycle Fluctuation; Panel Local Projection; Text Mining